Вирішення завдання оптимального вибору засобів захисту для корпоративної комп’ютерної мережі на основі методу аналізу ієрархій - Гонтар, Д. Ю. (ХНУРЕ, 2024)
This document presents a variant of solving the problem of optimal selection of security tools to create an effective integrated information security system for a small computer network of an enterprise using the T. Saaty hierarchy analysis method. The main optimality criteria are the residual risk and the level of implementation costs. In the course of the work, a hierarchical system was built, the priorities of each of the criteria were calculated, and the global priorities of the proposed security measures were determined. Based on the data obtained, the optimal complex for a given computer network of an enterprise was proposed.
Keywords: метод аналізу ієрархій; корпоративна комп’ютерна мережа